FATEMIYOUN: IRAN’S AFGHAN MILITIAS - Farzam, Rahimullah; Sarı, İsmail (Selcuk University, 2017)
This study examines the process by which Iranian Shiite Afghan citizens have been involved inthe war in Syria. In this context, it is tried to analyze that what kind of promises and motivationsthat the Shiite Afghans convinced by Iran to fight alongside the regime forces in the Syrian civilwar, how they were trained and the potential danger that these groups could create after the war. Iran mobilizes volunteer or mercenary Shiites from Afghanistan, Pakistan, India and Lebanonin the interests of their foreign policy to the war in Syria. It is known that Iran uses effectivelyapproximately 15 armed groups in Syria, mainly Hezbollah and Fatemiyoun Brigades, organisedunder various names. The mobilization of the Shiite population in other countries in Iran?s own wardated back to the Iran?Iraq war between 1980?88. Therefore, the use of the Shiite population is not anew phenomenon, as is the case in Iran?s Syrian case.

Bu çalışmada Şii Afgan vatandaşlarının İran tarafından Suriye’deki savaşa dahil olma süreciincelenmektedir. Bu bağlamda İran’ın hangi vaat ve motivasyonlarla Şii Afganları Suriye içsavaşında rejim güçlerinin yanında savaşmaya ikna ettiği, hangi süreçlerle eğittiği ve bu gruplarınsavaş sonrası oluşturabilecekleri potansiyel tehlike analiz edilmeye çalışılacaktır.İran, kendi dış politika çıkarları açısından Afganistan, Pakistan, Hindistan ve Lübnan’dangönüllü ya da paralı Şiileri silahlandırarak Suriye’deki savaşa mobilize etmektedir. İran’ın Suriye’deHizbullah ve Fatimiyyun Tugayları başta olmak üzere 15’e yakın silahlı grubu çeşitli adlar altındaörgütleyerek etkili bir şekilde kullandığı bilinmektedir. İran’ın kendi savaşında diğer ülkelerdeki Şiinüfusunu harekete geçirmesi 1980?88 İran?Irak savaşına kadar dayanmaktadır. Dolayısıyla İran’ınSuriye örneğinde de olduğu gibi Şii nüfusunu kullanması yeni bir olgu değildir.
FATİMİYYUN: İRAN’IN AFGAN MİLİSLERİ